Use of Narrow Band Imaging in the Diagnosis of Hypovascular Endobronchial Sarcoidosis. Issue 4 (October 2017) - Hakim, Rimoun; Sabath, Bruce; Kaplan, Tugba; Yung, Rex
Abstract : Narrow band imaging (NBI) has been widely applied for the evaluation of numerous disease conditions that present with increased vascularity of the mucosa, most often malignancies. It is increasingly being used in benign conditions as well. We present the first case in which NBI was used, rather, to detect areas of bronchial hypovascularity due to its ability to increase the visual contrast between normal and hypovascular mucosa. Endobronchial biopsy of these nodules led to the diagnosis of sarcoidosis. Had conventional white light alone been utilized, the diagnosis would likely have been missed because not only were these lesions difficult to visualize under white light but transbronchial lung biopsy and transbronchial needle aspiration were unremarkable. We propose that NBI should be considered in the bronchoscopic evaluation of possible sarcoidosis or any other condition that could present with airway hypovascularity.